Orofacial soft tissues actinomycosis: A retrospective, 10-year single-institution experience - Shinpei Matsuda; Hisato Yoshida; Hitoshi Yoshimura (Elsevier, 2021)
Background/purpose: Actinomycosis is a rare disease. It can often mimic other infectious or malignant diseases, and it is often misdiagnosed. Therefore, it is necessary to provide clinicians with clinical findings of patients with actinomycosis as many cases as possible. The aim of this study was to analyze the clinical features of actinomycosis of the orofacial soft tissues from the clinical data of the patients at the department in the past 10 years. Materials and methods: A retrospective study was designed, and the general characteristics of the patients, and the clinical characteristics of actinomycosis, including the initial diagnoses, the treatment methods, and the treatment outcomes, were studied. Results: Nine patients were included in the study. Initially, they were diagnosed with various diseases and treated by extraoral or intraoral surgical procedure with the administration of antibiotics. All patients were diagnosed with actinomycosis histopathologically, and lesions were cured. Conclusion: The diagnoses of actinomycosis is often challenging. The histopathologic examination may provide the most valuable information for clinicians than any other examination. In most cases of actinomycosis of the orofacial soft tissues, clinicians should consider the methods of treatment along with the administration of penicillin because it is a chronic disease and usually has a good prognosis.